Effects of Protective Surface Coating on Fluoride Release and Recharge of Recent Uncoated High-Viscosity Glass Ionomer Cement - Nantawan Krajangta; Chayanee Dulsamphan; Tongjai Chotitanmapong (Dentistry Journal, 2022)
The ability to release and recharge fluoride is a property of glass ionomer cement materials, which is an advantage for patients with a high caries risk. The purpose of this study was to evaluate the amount of released and recharged fluoride in recent uncoated high-viscosity glass ionomer cement (KetacTM Universal AplicapTM) with different surface coatings and at different time points. In total, 135 cylindrical-shaped specimens were equally divided into the following three groups: KetacTM Universal AplicapTM, KetacTM Molar AplicapTM, and KetacTM Fil Plus AplicapTM. The different coatings performed on each group were as follows: uncoated, coated with KetacTM Glaze, and coated with G-Coat PlusTM. The amounts of released and recharged fluoride were measured at 24 h and at weeks 1, 2, 3, and 4. The recharging agent was a 1.23% APF gel. KetacTM Universal AplicapTM showed the highest released fluoride at all time points and the highest recharged fluoride at weeks 1, 2, and 3. Both the KetacTM Glaze- and G-Coat PlusTM-coated specimens presented significantly lower released and recharged fluoride ions than the uncoated group at all time points (p < 0.001). Coating with G-Coat PlusTM significantly decreased the released and recharged fluoride compared to the coating with KetacTM Glaze at almost all time points (p < 0.05), except for weeks 1 and 2. The application of coating agents reduced the amount of released and recharged fluoride by the KetacTM Universal AplicapTM.